Production Potential of Broccoli (Brassica oleracea var. italica) in Hydroponics and Tilapia Based Aquaponics - Nadia, Zubyda Mushtari; Roy, Prosun; Salam, Md. Abdus (Journal of the Bangladesh Agricultural University, 2020)
Hydroponics is a plant growing procedure in water and aquaponics is an eco-friendly, water and energy-saving bio-integrated recirculating aquaculture system that integrates fish farming and vegetable gardening in a symbiotic close loop system. This experiment was carried to observe the production potentiality of broccoli in different type hydroponics like organic hydroponics (T1), inorganic hydroponics (T2) and tilapia based aquaponics systems (T3) each with three replicates for 106 days from 19th February to 4th June, 2018. Three kg vermicompost as T1 was soaked in 90 L water in a drum with a net bag and after that 1 kg vermicompost was added weekly discarding the old one. In case of T2, 28.50 g mixed fertilizer composed of 5g urea, 7.50g TSP, 5g MOP, 5g dolomite, 5g DAP, 0.50 g boron and 0.50 g iron were added in 90 L water and after seven days 22.80 g was added fortnightly. In the aquaponics tank, 10 healthy tilapia fingerlings were released in the same amount of water and 30% protein containing commercial floating feed was fed twice daily at the rate of 3% body weight. Sampling were carried out fortnightly for collecting different parameters of broccoli, fish and water quality. Significantly (P≤0.01) the highest broccoli production was found in T2 (11.79±0.51 tons/ha/106 days) followed by T3 (4.77±0.85 tons/ha/106 days) and the least was in T1 (2.24±0.14 tons/ha/106 days). The analysis showed that, the leaf area, root length and weight were statistically similar in all the three treatments. Fish production was 21.55±3.36 tons/ha/106 days. Nutritional composition of broccoli was also highest in T2 except moisture and ash content. Water dissolved oxygen, electrical conductivity, ammonia, nitrate, nitrogen and phosphorus concentration were suitable for growing broccoli in T2. Whereas in T3, ammonia concentration was high for fish. Broccoli production at higher temperature (31.40 to 36.00°C) in the laboratory than the optimum temperature was possible. Further experiment is needed to carry out in larger areas with different crops and fishes before extension in the field level. J Bangladesh Agril Univ 18(3): 768–778, 2020 https://doi.org/10.5455/JBAU.106528